ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH DI KABUPATEN/KOTA PROVINSI SUMATERA UTARA - Fitria, Rizky; Asnawi, Asnawi; Roni, Muhammad; Anwar, Khairil (Jurnal Ekonomi Regional Unimal, 2024)
The purpose of this study is to determine the magnitude of the influence of the independent variable on the dependent variable. The data used in this study is secondary data for 2017-2021 obtained from the Central Statistics Agency (BPS). The data analysis method in this study is panel data regression using Eviews 10. The results of this study show that Regional Taxes, Separated Regional Wealth Management Results, and Other Legal Local Original Revenues partially have a significant and positive effect on Local Original Revenues in the districts / cities of North Sumatra province, while Regional Levies do not have a significant and negative effect on Regional Original Revenue in districts / cities of North Sumatra province.